Self-Harm History, Anxiety-Depression, Severity of Disease, and Insight Are Significantly Associated With Suicide Risk in Forensic Psychiatric Inpatients of China - Guo, Huijuan; Zhong, Shaoling; Yue, Yuchen; Gou, Ningzhi; Sun, Qiaoling; Liang, Xiaoxi; Wang, Fanglan; Lu, Juntao; Li, Qiguang; Zhou, Jiansong; Wang, Xiaoping (Frontiers in Psychiatry, 2021)
Background: Forensic psychiatric patients have higher suicide risks than the general population. This study aimed to evaluate the extent of suicide risk and to explore the associated factors in forensic psychiatric inpatients in China. Methods: We conducted a cross-sectional study from 1st November, 2018 to 30th January, 2019 in the Forensic Psychiatric Hospital of Hunan Province, China. Patient’s information on socio-demographic, clinical and criminological characteristics was collected. The suicidality subscale of the MINI-International Neuropsychiatric Interview（M.I.N.I）, the Brief Psychiatric Rating Scale (BPRS), and the Severity of Illness of Clinical Global Impressions Scale (CGI-SI) were used to measure present suicide risks, psychiatric symptoms, and the severity of the patient's disease respectively. Binary logistic regression models were used to examine factors associated with suicide risk. Results: Twenty-one percent (84/408) of the forensic psychiatric inpatients reported suicide risk. Logistic regression analysis suggested that self-harm history (OR:3.47, 95% confidence interval CI: 1.45-8.33), symptoms of anxiety-depression (OR:1.15, 95% CI:1.04–1.27) and more severe mental disorder (OR:1.42, 95% CI:1.08-1.87) were associated with elevated suicide risk, while insight disorder (OR:0.81, 95% CI:0.65-0.99) was related to decreasing suicide risk. Conclusion: The study supplied useful clinical information to recognize high suicide risk in forensic psychiatric inpatients and may aid the development of valuable strategies for preventing and reducing suicide events.